Papaya (Carica papaya) mínimamente procesada fortificada con calcio por impregnación al vacío - Miñan Olivos, Guillermo Segundo (2021)
19th LACCEI International Multi-Conference for Engineering, Education, and Technology: “Prospective and trends in technology and skills for sustainable social development" "Leveraging emerging technologies to construct the future", Buenos Aires - Argentina, July 21-23.